ANALISIS PENGATURAN PUTARAN MOTOR INDUKSI 3 FASA DENGAN MENGATUR FREKUENSI MENGGUNAKAN VARIABLE SPEED DRIVE DI PT PDAM TIRTA MANGUTAMA KABUPATEN BADUNG - Putra Novantara, I Putu Adhe; Arta Wijaya, I Wayan; Suartika, I Made (Jurnal SPEKTRUM; Vol 8 No 4 (2021): Jurnal SPEKTRUM, 2022)
Along with the increase in technology and knowledge, this increase in the field of electric power systems makes the electric power system very developed. Electric motors have very important benefits in industry. In the operation of the electric machine, it is declared good when viewed from the performance of the motor. The purpose of this research is to find out what is the influence of the rotation of a 3-phase induction motor when setting the frequency on the speed and torque of VSD, as well as the effect of frequency on the amount of torque. The method used in this study is to take the rotational speed data measured by VSD and then compare it with the results of the analysis of the speed and torque calculations. The results of the study based on the frequency setting on the VSD Display at PT.PDAM Tirta Mangutama Belusung Area. The results of the VSD settings obtained frequency values of 30 Hz, 35 Hz, 40 Hz and 45 Hz. Calculations using the equation of motor rotation speed to frequency, the theoretical value is compared to 900rpm and from the results of calculations using VSD is no difference, which is 900rpm. So from these data it can be seen that the data practically shows results that are in accordance with the theory so that it can be concluded that the performance of the induction motor is in good condition.